Government procurement toolkit : R.A. No. 9184, annotated - Ursal, Sofronio B. (Philippines : Good Governance Books, 2004)
A dictionary definition of the word "tool" is any instrument necessary to the efficient prosecution of one's profession or trade, and "kit" as a collection of tools for a special purpose. Hence this book is recently approve government procurement reform act, and designed as a primary reference source for the use of the heads of the various procuring entities.
Part One. Overview of government procurement -- Part Two. Receipt and opening of bids -- Part Three. Award, implementation and termination of the contract -- Part Four. Protest mechanism.
Includes index.
Keywords: GOVERNMENT -- PURCHASING -- LAW